Development of Eco-Friendly Chemistry Teaching Materials: A Periodic Table Using Recycled Materials - Marfu’ah, Siti; Amelia, Lupita; Mitra, Andini; Amalia, Shela; Setyorini, Titis A.; Alifah, Karimatul (Proceeding International Conference on Religion, Science and Education, 2025)
Chemistry education, particularly in learning the periodic table, requires instructional media that can visualize abstract concepts and facilitate students’ understanding of the arrangement of chemical elements. This study aims to develop periodic table learning media using recycled materials, including cardboard and styrofoam. The development followed an exploratory approach through prototype creation, involving six students and one chemistry education lecturer. The development process consisted of three main stages: (1) needs analysis, including literature review and material characteristics analysis; (2) design, involving blueprint creation and technical specification setting; and (3) prototype development, consisting of material preparation, component fabrication, and assembly. The study resulted in a modular periodic table prototype measuring 70 cm x 100 cm, with removable element cards sized 8 cm x 8 cm. The developed learning media offers advantages in interactivity through its modular system, visualization through consistent color usage for element grouping, and sustainability through the use of recycled materials. Challenges in development included optimizing material durability and the locking system for element cards. The resulting prototype shows potential to support active and constructive learning while integrating principles of education for sustainable development in chemistry learning.